Antisludging agent charge device in reverse osmosis desalinized water system based on reuse of reclaimed water - ZHANG LIANG; LIU XUELEI (2018)
The utility model provides an antisludging agent charge device in reverse osmosis desalinized water system based on reuse of reclaimed water, including the under casing, electric telescopic handle, extend the case, delivery pump no. 1, communicating pipe, slope spray line no. 1, dilute the case, delivery pump no. 2, stirred tubular and stirring board, electric telescopic handle is installed to theunder casing outer end, the case outer end is being extended in the electric telescopic handle assembly, it installs in the under casing upper end to extend the case, and extend to inside the under casing, extend the case upper end and install delivery pump no. 1, the space size that adjustable extension case of this design and under casing constitute, install communicating pipe and diluting thecase left end, it has slope spray line no. 1 to dilute incasement portion left side wall mounting, it is connected with slope spray line no. 1 to pass dilutent case communicating pipe, it is providedwith delivery pump no. 2 to